Autonomous Surveillance Drone - Prof. Dr. Kaushika Patel; Yash Sojitra (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This paper presents the design, development, and testing of a fully autonomous surveillance drone built using a quadcopter frame, Brushless DC (BLDC) motors, Electronic Speed Controllers (ESCs), Raspberry Pi 4, GPS, and a Pixhawk flight controller. The drone achieves autonomous navigation using telemetry communication and DroneKit-MAVProxy, a Python-based software framework, in conjunction with ground control tools like QGroundControl and Mission Planner. The goal is to create a low-cost, user-friendly UAV (Unmanned Aerial Vehicle) capable of performing tasks like area monitoring, GPS-based navigation, and data collection. Reliable testing was conducted to assess flight stability, GPS accuracy, communication range, and mission execution success. The results confirm the drone’s reliability in open-field scenarios, with potential for future enhancements such as AI-based object detection, collision avoidance, and multi-drone swarm operation